“It Is Utterly Out of My Expectation”-A Case Inquiry of Teacher Identity of an EFL Teacher in a Chinese Shadow School Setting - Wang, Feng; Guo, Jingwen; Wu, Bin; Lin, Zhong (Frontiers in Psychology, 2021)
Though teacher identity is currently receiving an increasing amount of attention in the literature on teacher education and teacher development, little information is available about the richness, fluidity and individuality of EFL teacher identities in various L2 settings, as reviewed by Moussu and Llurda (2008). This preliminary case inquiry has echoed that comment by exploring qualitatively how language teacher identity features in the participant’s categorization of herself as a professional during her school-to-work transition at a shadow school in hinterland China. Drawing on semi-structured interviews and reflection essays, the triangulated data were analyzed with thematic analysis in order to find categories of enacted identities and key factors that impacted Jane’s teacher identity formation. The results indicate four identities existed: an attendant, a firefighter, a coolie and a tramp. The fundamental predicaments hovering over the green employer encompass an array of contextual factors, including 1) overwhelming anxieties for potential early student leavers; 2) overhuge workload and fluid working schedule; 3) endless non-teaching related commitments; 4) lack of career prospect and development ladder. The results of the study contribute to the understanding of the complex and dynamic nature of teacher identity influenced by sociocultural landscapes where language teachers are situated. The research suggests implications for teacher educators and stakeholders on how to transform a novice to a qualified EFL teacher within the ideology and discouraging discourse of a burgeoning privately-owned training market, and on how to mediate green teachers’ agency and autonomy against the bottlenecks of their initial years of teaching.